(untitled) (Arquivos em Odontologia, 2025)
Aim: This study aimed to evaluate the biomechanical preparation quality (instrumented surface i.e. percentage of canal walls touched, increase in canal volume) and instrumentation time using a rotary file developed for deciduous teeth (Sequence Baby File - SBF) and compaired to conventional manual files (K file). Methods: For this in vitro study, 20 resin prototypes of mandibular deciduous molars were included in the sample, focusing on the mesial canals, totaling 40 canals. Initially, these prototypes underwent scanning via micro-computed tomography (micro-CT) and then were randomly assigned to two groups: SBF (G1) and K file (G2), with 20 canals in each group. The total instrumentation time was meticulously recorded. Following the preparation phase, a subsequent scan was conducted and the images were reconstructed and aligned with the initial scans. Utilizing the CTan® program measurements were taken concerning canal volume and the percentage of canal walls touched (surface area). Student’s T-test and Mann-Whitney U test were used for statistical analysis (p < 0.05). Results: No statistically significant differences were found in volume and surface area at the analyzed data between the two groups under study. Time was statistically significant shorter in SBF (G1) (p < 0.05). Conclusion: The findings of this study underscore that rotary files developed for primary teeth (SBF – G1) yield comparable outcomes to K files (G2) in terms of biomechanical canal preparation, all achieved in a shorter instrumentation timeframe. These results offer an encouraging perspective for pediatric dentists considering the adoption of such system. Uniterms: pediatric dentistry; pulpectomy; endodontics; x-ray microtomography.